The impact of HIV and ART exposure during pregnancy on fetal growth: a prospective study in a South African cohort - Asanda Mtintsilana; Shane A. Norris; Siphiwe N. Dlamini; Lukhanyo H. Nyati; David M. Aronoff; John R. Koethe; Jeffrey A. Goldstein; Alessandra Prioreschi (BMC, 2023)
Abstract Background In utero exposure to human immunodeficiency virus (HIV) and antiretroviral (ART) is associated with adverse birth outcomes, which are often attributed to alterations in placental morphology. This study used structural equation models (SEMs) to examine the impact of HIV and ART exposure on fetal growth outcomes and whether these associations are mediated by placental morphology in urban-dwelling Black South African women. Methods This prospective cohort study included pregnant women living with HIV (WLWH, n = 122) and not living with HIV (WNLWH, n = 250) that underwent repeated ultrasonography during pregnancy, and at delivery, to determine fetal growth parameters in Soweto, South Africa. The size and the velocity of fetal growth measures (i.e., head and abdominal circumference, biparietal diameter, and femur length) were calculated using the Superimposition by Translation and Rotation. Placenta digital photographs taken at delivery were used to estimate morphometric parameters and trimmed placental weight was measured. All WLWH were receiving ART for the prevention of vertical transmission of HIV. Results A trend towards a lower placental weight and significantly shorter umbilical cord length was reported in WLWH compared to their counterparts. After sex stratification, umbilical cord length was significantly shorter in males born to WLWH than in male fetuses born to WNLWH (27.3 (21.6-32.8) vs. 31.4 (25.0-37.0) cm, p = 0.015). In contrast, female fetuses born to WLWH had lower placental weight, birth weight (2.9 (2.3-3.1) vs. 3.0 (2.7-3.2) kg), and head circumference (33 (32-34) vs. 34 (33-35) cm) than their counterparts (all p ≤ 0.05). The SEM models showed an inverse association between HIV and head circumference size and velocity in female fetuses. In contrast, HIV and ART exposure was positively associated with femur length growth (both size and velocity) and abdominal circumference velocity in male fetuses. None of these associations appeared to be mediated via placental morphology. Conclusion Our findings suggest that HIV and ART exposure directly affects head circumference growth in females and abdominal circumference velocity in male fetuses; but may improve femur length growth in male fetuses only.